2011
DOI: 10.1111/j.2042-3292.2010.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Osseous cyst-like lesions/subchondral bone cysts of the phalanges

Abstract: Summary In the horse, the phalanges are the second most common location for the occurrence of osseous cyst‐like lesions (OCLLs) after the medial femoral condyle of the stifle. Phalangeal OCLLs occur in a variety of locations, most of which are adjacent to, if not communicating with, a joint. The aetiology of these lesions is considered to be multifactorial by most authors. Horses with OCLLs demonstrate lameness of varying severity. Diagnostic analgesia should be used to localise the lameness. After localisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 58 publications
2
37
1
1
Order By: Relevance
“…tumour necrosis factor‐alpha [TNF‐α]) associated with the soft tissues lesions in the adjacent DSIL and the DDFT . This supports the hypothesis that insertional desmopathy or tendonopathy can induce osseous resorptive lesions . The involvement of both the DSIL and DDFT seen histopathologically is not only consistent with the location of the osseous resorptive lesions identified on MR but also provides further evidence that these structures often respond to stress placed upon the foot as a single functional unit .…”
Section: Discussionsupporting
confidence: 62%
“…tumour necrosis factor‐alpha [TNF‐α]) associated with the soft tissues lesions in the adjacent DSIL and the DDFT . This supports the hypothesis that insertional desmopathy or tendonopathy can induce osseous resorptive lesions . The involvement of both the DSIL and DDFT seen histopathologically is not only consistent with the location of the osseous resorptive lesions identified on MR but also provides further evidence that these structures often respond to stress placed upon the foot as a single functional unit .…”
Section: Discussionsupporting
confidence: 62%
“…Various pathogenic processes have been implicated in the occurrence of SCLs, with trauma being the likely cause in mature horses (Sherlock and Mair 2011) and osteochondrosis in juvenile horses (Verschooten and De Moor 1982). In the cases described herein, a developmental aetiology was suspected based on the young age and the bilateral occurrence in two of the three horses affected, and lack of any history of trauma (Verschooten and De Moor 1982).…”
Section: Discussionmentioning
confidence: 90%
“…Overall, the prognosis for return to performance for horses with phalangeal SCLs ranges from 30 -90 %, but is largely dependent on the age, treatment regime, location of the SCL, and concurrent osteoarthritis (Sherlock and Mair 2011). Smith et al (2005) have suggested that older horses, and those with pre-existing osteoarthritis, have a significantly poorer prognosis following surgical debridement of femoral SCLs, with only 35 % of horses older than 3 years returning to soundness after debridement.…”
Section: Discussionmentioning
confidence: 99%
“…), the talus (Montgomery and Juzwiak ) and the phalanges (Story and Bramlage ; Smith et al . ; Sherlock and Mair ).…”
Section: Introductionmentioning
confidence: 99%
“…). Subchondral bone cysts show marked variation in size and shape; they may be shallow or deep (>10 mm) and may be domed, conical or spherical in shape (Sherlock and Mair ). Grossly, these cysts have a fibrous lining and contain fibrous tissue, with or without synovial gelatinous material.…”
Section: Introductionmentioning
confidence: 99%